1997
DOI: 10.3109/10428199709109163
|View full text |Cite
|
Sign up to set email alerts
|

Activity of 2-chlorodeoxyadenosine (cladribine) in 2-hour intravenous infusion in 94 previously treated patients with low grade non-hodgkin's lymphoma

Abstract: The purpose of our study was to determine the efficacy of 2-chlorodeoxyadenosine (2-CdA) administered in 2-hour intravenous infusions in previously treated patients with low grade non-Hodgkin's lymphoma (LGNHL). We treated 94 LGNHL patients with 2-CdA at a dosage of 0.12 mg/kg/24h in 2-hour intravenous infusion for 5 consecutive days. The treatment consisted of from 1 to 7 courses (median 3), repeated usually at monthly intervals. All patients were refractory to or relapsed after standard chemotherapy. Of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 22 publications
2
25
1
Order By: Relevance
“…27 These results were later reproduced in a trial where 80% of patients had a nonfollicular histology, mainly lymphoplasmacytic lymphoma (37%) or B-chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (29%). 28 Of 94 patients, 48 (51%) achieved a response and 12 (13%) had a CR. The median duration of response was 12 months for a CR and 6 months for a partial response.…”
Section: Single-agent Therapy In Previously Treated Indolent Nhlmentioning
confidence: 97%
See 1 more Smart Citation
“…27 These results were later reproduced in a trial where 80% of patients had a nonfollicular histology, mainly lymphoplasmacytic lymphoma (37%) or B-chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (29%). 28 Of 94 patients, 48 (51%) achieved a response and 12 (13%) had a CR. The median duration of response was 12 months for a CR and 6 months for a partial response.…”
Section: Single-agent Therapy In Previously Treated Indolent Nhlmentioning
confidence: 97%
“…[26][27][28][29][30][31][32][33][34][35][36] Cladribine demonstrated impressive activity with overall and CR rates of up to 72% and 38%, respectively. Follicular and nonfollicular histologies appeared to be equally responsive.…”
Section: Single-agent Therapy In Previously Treated Indolent Nhlmentioning
confidence: 99%
“…These results seem to be superior to those achieved earlier with 2-CdA alone, as reported by us and by other authors. [22][23][24] The RC/ RCC regimens also seem at least to be equally as efficient as 2-CdA in combination with cyclophosphamide and prednizone 25 and cyclophosphamide combined with either mitoxantrone 26 or etoposide. 27 Laurencet et al 25 reported a response in 88% patients, including 4 CRs among 19 patients who received 2-CdA combined with cyclophosphamide and prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] Initial trials with 2-CdA established a maximal tolerated dose of 0.1 mg/kg per day as a continuous intravenous infusion over 7 days 23 ; however, because of its long half-life, bolus, subcutaneous, and oral regimens have been equally effective. 7,8,12,13,[15][16][17][24][25][26][27] Reported toxicities consist primarily of myelosuppression and bacterial and opportunistic infections, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] with less frequent occurrences of autoimmune hemolytic anemia 28 and neurotoxicity. 29 Rare reports of an increased incidence of second malignancies or transformation to aggressive NHL have not been confirmed.…”
Section: Conclusion 2-mentioning
confidence: 99%
“…2-Chlorodeoxyadenosine (2-CdA) (cladribine, Leustatin) is a deoxyadenosine purine nucleoside analog that is toxic to both proliferating and resting lymphocytes (for review, see Tallman and Hakimian 1 ), with activity in chronic lymphocytic leukemia (CLL), 2,3 lowgrade NHL, [4][5][6][7][8][9][10][11][12][13][14][15][16][17] and hairy cell leukemia (HCL). [18][19][20][21][22] Initial trials with 2-CdA established a maximal tolerated dose of 0.1 mg/kg per day as a continuous intravenous infusion over 7 days 23 ; however, because of its long half-life, bolus, subcutaneous, and oral regimens have been equally effective.…”
Section: Conclusion 2-mentioning
confidence: 99%